2022
DOI: 10.3390/ma15041284
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromium Carbide Coatings on Microstructure and Thermal Conductivity of Mg/Diamond Composites Prepared by Squeeze Casting

Abstract: Magnesium matrix composites are considered a desired solution for lightweight applications. As an attractive thermal management material, diamond particle-reinforced Mg matrix (Mg/diamond) composites generally exhibit thermal conductivities lower than expected. To exploit the potential of heat conduction, a combination of Cr coating on diamond particles and squeeze casting was used to prepare Mg/diamond (Cr) composites. The thickness of the Cr coating under different coating processes (950 °C/30 min, 950 °C/60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Adding 20wt.%AlN decreases the TC at room temperature by 3.5%, from 129.7 W/(m•K) to 125.1 W/(m•K) in this study. Li et al [9] have reported a similar phenomena of TC reduction in Dia/Mg composites. Even diamond with a TC of up to 2000W/(m•K) cannot improve the TC of magnesium alloys in the absence of surface treatment.…”
Section: Microstructure Of Compositesmentioning
confidence: 63%
See 1 more Smart Citation
“…Adding 20wt.%AlN decreases the TC at room temperature by 3.5%, from 129.7 W/(m•K) to 125.1 W/(m•K) in this study. Li et al [9] have reported a similar phenomena of TC reduction in Dia/Mg composites. Even diamond with a TC of up to 2000W/(m•K) cannot improve the TC of magnesium alloys in the absence of surface treatment.…”
Section: Microstructure Of Compositesmentioning
confidence: 63%
“…By combining these components with magnesium-based materials, composites with excellent TC and minimal CTE may be produced. Li et al [9] combined Cr-coated diamond and pure magnesium utilizing the pressure infiltration approach to produce magnesium-based composites with improved thermal properties. This Dia/Mg composite achieved TC of 202.42 W/(m•K) at room temperature with CTE of 5.82×10 -6 K -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a poor interfacial connection between the copper and the diamonds is indicated by the presence of large cracks at the boundaries and the majority of the diamond particles being exposed on the fracture surfaces. The literature survey implies that the use of Cr-coating can efficiently enhance the interfacial bonding between the particles and the matrix, which in turn makes it easier to densify composite materials as a whole [13]. However, the addition of higher content of diamond particles and reinforcement can make the densification more complicated because there is no suitable matrix that can fill in the spaces created by the adjacent diamond particles, there is a very low relative density when the particle concentration is exceeded.…”
Section: Preparation Of Copper/diamond Compositementioning
confidence: 99%
“…In addition to the research above, several carbon materials have also been studied. By coating TiC or Cr on diamond, the thermal conductivity of diamond/Mg composites is significantly improved [106,107]. Olszówka-Myalska et al [108] applied amorphous carbon with an irregular shape as the reinforcement and coated it with SiO 2 by the sol-gel method.…”
Section: Other Carbon Reinforcementsmentioning
confidence: 99%